Characteristics and Level of Dependence of Stroke Patients at dr. Soekardjo Hospital, Tasikmalaya - Teti Agustin; Asep Robby; Eri Triana Ramadhan (LP3M Universitas Muhammadiyah Tasikmalaya, 2023)
Stroke is an acute global and focal brain function disorder caused by obstruction of blood circulation to the brain where there is a blockage or rupture of blood vessels in the brain, so that the supply of oxygen and nutrients is disrupted. The purpose of this study was to determine the level of dependence of stroke patients undergoing treatment in the Melati 2B room at RSUD dr. Soekardjo City of Tasikmalaya. This research method is descriptive quantitative with a population of stroke sufferers in the jasmine room 2B RSUD dr. Soekardjo City of Tasikmalaya. The sampling technique used accidental sampling, namely as many as 5 people. Based on the results of the study it was known that the characteristics of the respondents were: male sex as many as 3 people (60%) and women as many as 2 people (40%). The results of this study indicated that there were 3 respondents with a partial care dependency level (60%), respondents with a total care dependence level of 2 respondents (40%), while there were no respondents with a minimal care dependency level.